2022
DOI: 10.12982/cmujns.2022.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Heat Treatment for Resistant Starch Levels and Prebiotic Properties of High Carbohydrate Foods: Meta-Analysis Study

Abstract: Microwave heat treatment is one of the most widely used starch physical modification techniques in analyzing the increase in resistant starch levels in foodstuffs. However, this technique has varying effects on each type of high-carbohydrate food. This study aims to analyze the type of carbohydrate food that significantly increases the levels of resistant starch and prebiotic properties by the microwave heat treatment technique. This study used 31 articles that were analyzed and selected through the PRISMA gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results analysed were pooled RMD values (95% CI and p-values) and heterogeneity (I 2 ) by means of a random-effects model. Isra et al (2022) and Higgins & Thompson (2002) reported that the heterogeneity exploration across studies was carried out using the index I 2 (I 2 > 50% indicates good heterogeneity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results analysed were pooled RMD values (95% CI and p-values) and heterogeneity (I 2 ) by means of a random-effects model. Isra et al (2022) and Higgins & Thompson (2002) reported that the heterogeneity exploration across studies was carried out using the index I 2 (I 2 > 50% indicates good heterogeneity).…”
Section: Discussionmentioning
confidence: 99%
“…Isra et al . (2022) and Higgins & Thompson (2002) reported that the heterogeneity exploration across studies was carried out using the index I 2 ( I 2 > 50% indicates good heterogeneity).…”
Section: Methodsmentioning
confidence: 99%
“…In a meta-analysis of 31 articles investigating the effect of microwave treatment on starch content of high-carbohydrate foods, Isra et al highlighted that this method of cooking significantly increased the level of RS, whatever the food matrix [2.755% (95% CI: 2.106 to 3.403); p < 0.001]. Moreover, RS enrichment resulted in enhanced prebiotic properties, based on several parameters, namely starch composition, amylose interaction, lactic acid bacteria viability, and enteropathogenic Escherichia coli viability ( 36 ).…”
Section: Methodsmentioning
confidence: 99%